Simulation of Worm Pair Transmission Accuracy of TK13250E NC Rotary Table based on Adams - Wang Feng; Chen Jie; Hong Rongjing (Jixie chuandong)
Based on the numerical controlled (NC) rotary table of TK13250E，the influence of various errors of the worm gear and worm of the transmission mechanism of the NC rotary table on the transmission precision is studied. The dynamics simulation software Adams is used to simulate the worm pair. The simulation results are compared with the ideal results，which verify the correctness of the virtual prototype model. The material error，manufacturing error，use error and their random synthesis error of the worm pair are simulated by Adams and the influence degree of different errors on accuracy is obtained. In order to study the law of accuracy deterioration of NC under excessive load，the accelerated wear test of precision decline of NC rotary table is designed. The test shows that with the increase of worm gear wear，the positioning accuracy and repetitive positioning accuracy of NC rotary table begin to decline.